METHODOLOGICAL ASPECTS OF CONNECTION OF MIND MAPS WITH INTERACTIVE WHITEBOARD IN EDUCATIONAL PROCESS - SLAMA, Jaroslav (Trends in education, 2009)
The article deals with possible connections of mind maps, mind mapping software and interactive whiteboard within educational process. The article offers evaluation of the main methodological aspects when creating interactive mind map and presents recommendations according to phases of interactive mind map production.
Keywords: interactive whiteboard; mind map; information and communication technology; interactive mind map; web 2.0; creative thinking; creativity; motivation; didactic method.